Kewenangan Konstitusional Mahkamah Konstitusi Dalam Memutus Sengketa Hasil Pemilu Dan Pilkada Serentak - Ofis Rikardo; Viranti Nur Ikhwan; Fani Larasati (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2023)
Decision of the Constitutional Court Number 14/PUU-XI/2013 provides legal implications for the implementation of elections (elections for DPR, DPD, President and Vice President, and DPRD members). The election for members of the representative body which was previously held earlier than the election for the president and vice president, based on this decision of the constitutional court, the election for members of the representative body and the election for president and vice president will be held concurrently. The concurrent elections and local elections which will be held in 2024 have the potential to cause disputes over the results which will lead to the resolution of disputes over election results at the Constitutional Court. With the constitutional authority possessed by the Constitutional Court, the Constitutional Court is required to be able to resolve disputes over election and local election results in order to maintain elections and local elections that are direct, general, free, secret, honest and fair as mandated by the 1945 Constitution.